UiTM Law Newsletter (Jan - Apr 2019) - UiTM Shah Alam, Faculty of Law (Faculty of Law, 2019)
UiTM Law is more than pleased to officially launch the inaugural issue of its quarterly newsletter. Ever since its establishment, UiTM Law has developed into a strong autonomous and integrated academic community of academic staff and students that have incorporated into a leading university network. Being a faculty consisting of members from wide–ranging expertise, knowledge and skills, there are numerous activities, diverse programmes as well as achievements occurring within our community. We hope to share these exciting activities as well as distinguished achievements through the upcoming issues of our newsletter. Our activities have expanded in depth and breadth in response to the increasing sophistication and internationalization of the education fraternity in Malaysia. Our upcoming issues would also present our continuous improvements and innovations, which would hopefully contribute to further development of UiTM Law.